IMPLEMENTATION OF ADVANCED PEDAGOGICAL TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Raxmatova, Go'zaloy (Журнал иностранных языков и лингвистики, 2021)
Annotation. This article explores the role of modern pedagogical technologies in developing the communicative competence of students in learning a foreign language, as well as which are the most productive for creating an educational sphere, and ensuring personal-oriented interaction of all participants in the educational process. Key words: pedagogical technologies, communicative competence, personallyoriented interaction, participants, productive.